Pendidikan Kaul Ketaatan bagi Biarawan Generasi Z: Studi Kasus di Biara Skolastikat MSC Pineleng - Gregorius Hertanto Dwi Wibowo; Sergius Mila (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
The purpose of this study is to discover how the religious of Z-generation live the vow of obedience; what are the particular challenges and difficulties they experience, especially facing the challenges of that digital technological world. The Era of Generation Z is characterized by people's dependence on digital technology and the internet. The results of these technological advances have had an impact on many aspects of life both visible and related to the inner world. Inevitably religious who profess the three vows also receive its influence. The conveniences offered by technology and the temptations associated with human freedom pose a challenge to a life of vowed obedience, especially for the younger generation of religious. Using Qualitative Research Method of case study type, the researcher examines the problematics of obedience in the MSC Scholasticate Community. The results of this study provide a descriptive picture of the characteristics of living the vow of obedience among Z-generation religious and suggestions for better education of the vow of obedience.